2019
DOI: 10.1002/mdc3.12781
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functional Abilities in Parkinson's Disease: Agreement Between Patients and Informants

Abstract: Background The Penn Parkinson's Daily Activities Questionnaire‐15 (PDAQ‐15) assesses cognition‐related instrumental activities of daily living (IADL) in Parkinson's disease (PD). Objectives To assess the degree and predictors of disagreement between patients (PT) and knowledgeable informants (KI) on the PDAQ‐15. Methods We recruited 254 PT and KI pairs (PT‐KI), determined predictors of agreement, and compared scores to a performance‐based functional measure (Direct Assessment of Functional Status [DAFS]; N = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(76 reference statements)
3
17
1
Order By: Relevance
“…Although we found overall moderate agreement between participant and study partner reports in general, it was notably lower for participants diagnosed with PD‐MCI. A recent study aimed at assessing the degree of difference between participants and study partners on the PDAQ‐15 found discrepancies among the 2 groups that grew with increasing cognitive impairment . Conversely, we found the weakest correlation between the 2 sources to be within the PD‐MCI group, again potentially because of the overall higher global cognitive abilities in our cognitively impaired groups.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Although we found overall moderate agreement between participant and study partner reports in general, it was notably lower for participants diagnosed with PD‐MCI. A recent study aimed at assessing the degree of difference between participants and study partners on the PDAQ‐15 found discrepancies among the 2 groups that grew with increasing cognitive impairment . Conversely, we found the weakest correlation between the 2 sources to be within the PD‐MCI group, again potentially because of the overall higher global cognitive abilities in our cognitively impaired groups.…”
Section: Discussioncontrasting
confidence: 50%
“…A recent study aimed at assessing the degree of difference between participants and study partners on the PDAQ-15 found discrepancies among the 2 groups that grew with increasing cognitive impairment. 26 Conversely, we found the weakest correlation between the 2 sources to be within the PD-MCI group, again potentially because of the overall higher global cognitive abilities in our cognitively impaired groups. Our results suggest that participants with PD-MCI may be more acutely aware of cognitive changes and how they may subtly impact IADLs.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A range of performance-based tests already exist and some of them have been used in PD cohorts. However, they are either timeconsuming in either assessment and/or scoring [Direct Assessment of Functional Status (Brennan et al, 2016;Deck et al, 2019); Older Americans Resources and Services scale (Shulman et al, 2006); Naturalistic Action Test (Roll, Giovannetti, Libon, & Eppig, 2019); Financial capacity instrument (FCI) (Martin et al, 2013); Medication Management Ability Assessment (Pirogovsky et al, 2013); Multiple Object Test (MOT) (Beyle et al, 2018;Glonnegger et al, 2016)], need extraordinary materials [Six activities task (Fellows & Schmitter-Edgecombe, 2019)], are assessed in a domestic environment [Performance Assessment of Self-Care Skills, (Foster, 2014)], correlate with PD-related motor symptoms [University of California San Diego Performance-Based Skills Assessment, UPSA (Holden et al, 2018)], or motor influences on the performance-based test have not been examined in PD studies yet [Timed Instrumental Activities of Daily Living scale (Higginson, Lanni, Sigvardt, & Disbrow, 2013)]. In Alzheimer's disease research, a performance-based test for mild cognitive impairment (MCI) and early dementia was recently developed: the Erlangen Test of Activities of Daily Living in Persons with Mild Dementia and Mild Cognitive Impairment (ETAM).…”
Section: Introductionmentioning
confidence: 99%